The cytotoxicity of the α1-adrenoceptor antagonist prazosin is linked to an endocytotic mechanism equivalent to transport-P. (2nd December 2015) - Fuchs, Robert; Stracke, Anika; Ebner, Nadine; Zeller, Christian Wolfgang; Raninger, Anna Maria; Schittmayer, Matthias; Kueznik, Tatjana; Absenger-Novak, Markus; Birner-Gruenberger, Ruth
Abstract: Since the α1-adrenergic antagonist prazosin (PRZ) was introduced into medicine as a treatment for hypertension and benign prostate hyperplasia, several studies have shown that PRZ induces apoptosis in various cell types and interferes with endocytotic trafficking. Because PRZ is also able to induce apoptosis in malignant cells, its cytotoxicity is a focus of interest in cancer research. Besides inducing apoptosis, PRZ was shown to serve as a substrate for an amine uptake mechanism originally discovered in neurones called transport-P. In line with our hypothesis that transport-P is an endocytotic mechanism also present in non-neuronal tissue and linked to the cytotoxicity of PRZ, we tested the uptake of QAPB, a fluorescent derivative of PRZ, in cancer cell lines in the presence of inhibitors of transport-P and endocytosis. Early endosomes and lysosomes were visualised by expression of RAB5-RFP and LAMP1-RFP, respectively; growth and viability of cells in the presence of PRZ and uptake inhibitors were also tested. Cancer cells showed co-localisation of QAPB with RAB5 and LAMP1 positive vesicles as well as tubulation of lysosomes. The uptake of QAPB was sensitive to transport-P inhibitors bafilomycin A1 (inhibits v-ATPase) and the antidepressant desipramine. Endocytosis inhibitors pitstop ® 2 (general inhibitor of endocytosis), dynasore (dynamin inhibitor) and methyl-β-cyclodextrin (cholesterol chelator) inhibited the uptake of QAPB. Bafilomycin A1 and methyl-β-cyclodextrin but not desipramine were able to preserve growth and viability of cells in the presence of PRZ. In summary, we confirmed the hypothesis that the cellular uptake of QAPB/PRZ represents an endocytotic mechanism equivalent to transport-P. Endocytosis of QAPB/PRZ depends on a proton gradient, dynamin and cholesterol, and results in reorganisation of the LAMP1 positive endolysosomal system. Finally, the link seen between the cellular uptake of PRZ and cell death implies a still unknown pro-apoptotic membrane protein with affinity towards PRZ.